Upaya Perlindungan Hukum Bagi Santri Pondok Pesantren Al Muhajirin Dalam Mencegah Kasus Perundungan - Moh Kamaluddin; Ratih Dwi Pangestu; Sunari Sunari; Wyda Lusiana; Lucius Andik Rahmanto; Ana Indrawati; Lambang Siswandi (Hakim, 2023)
Bullying is an act that really lowers a person's self-esteem. There are many cases of bullying, especially in the world of education, including in Islamic boarding schools. The rise of this bullying phenomenon has caused us as lecturers to become concerned and then carry out legal counseling with the title legal protection efforts for students at al Muhajirin Islamic boarding schools in preventing cases of bullying. As for the results, no cases of bullying have been found at the Al Muhajirin Islamic boarding school